Pictorial Guides of Malaysian Primates : Conservation Perspectives - Badrul Munir, Md Zain; Mohd Ridwan, Abd Rahman; Roberta Chaya Tawie, Tingga; Millawati, Gani (Faculty of Science and Technology, Universiti Kebangsaan Malaysia, 2024)
Malaysia is rich in biodiversity and is home to 26 primate species distributed throughout the country. Thirteen primate species can be found in Peninsular Malaysia, whereas another 15 species are present in Sabah and Sarawak. There is an urgent need to document Malaysian primate diversity through a pictorial guide that will use photos and descriptions for the identification and conservation of Malaysian primate species. This book highlights the natural treasures of Malaysia and describes the primate diversity in Peninsular Malaysia, Sabah and Sarawak. This book provides fundamental information about each primate species in Malaysia and discusses their conservation perspectives along with future research opportunities.